Scaling-Up eConsult: Promising Strategies to Address Enabling Factors in Four Jurisdictions in Canada - Mylaine Breton; Catherine Lamoureux-Lamarche; Mélanie Ann Smithman; Erin Keely; Maxine Dumas Pilon; Alexander Singer; Gerard Farrell; Paula Bush; Catherine Hudon; Lynn Cooper; Véronique Nabelsi; Élizabeth Côté-Boileau; et al. (Kerman University of Medical Sciences, 2023)
Background  Effective healthcare innovations are often not scaled up beyond their initial local context. Lack of practical knowledge on how to move from local innovations to large-system improvement hinders innovation and learning capacity in health systems. Studying scale-up processes can lead to a better understanding of how to facilitate the scale-up of interventions. eConsult is a digital health innovation that aims to connect primary care professionals with specialists through an asynchronous electronic consultation. The recent implementation of eConsult in the public health systems of four Canadian jurisdictions provides a unique opportunity to identify different enabling strategies and related factors that promote the scaling up of eConsult across jurisdictions.Methods  We conducted a narrative case study in four Canadian provinces, Quebec, Ontario, Manitoba, and Newfoundland & Labrador, over a 3-year period (2018-2021). We observed provincial eConsult committee meetings (n = 65) and national eConsult forums (n = 3), and we reviewed internal documents (n = 93). We conducted semistructured interviews with key actors in each jurisdiction (eg, researchers, primary care professionals, specialists, policy-makers, and patient partners) (n = 40). We conducted thematic analysis guided by the literature on factors and strategies used to scale up innovations.Results  We identified a total of 31 strategies related to six key enabling factors to scaling up eConsult, including: (1) multi-actor engagement; (2) relative advantage; (3) knowledge transfer; (4) strong evidence base; (5) physician leadership; and (6) resource acquisition (eg, human, material, and financial resources). More commonly used strategies, such as leveraging research infrastructure and bringing together various actors, were used to address multiple enabling factors.Conclusion  Actors used various strategies to scale up eConsult within their respective contexts, and these helped address six key factors that seemed to be essential to the scale-up of eConsult.